2022
DOI: 10.2147/jir.s349981
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Camellia fascicularis Polyphenols via Attenuation of NF-κB and MAPK Pathways in LPS-Induced THP-1 Macrophages

Abstract: Plant polyphenols possess beneficial functions against various diseases. This study aimed to identify phenolic ingredients in Camellia fascicularis (C. fascicularis) and investigate its possible underlying anti-inflammatory mechanism in lipopolysaccharide (LPS)-induced human monocytes (THP-1) macrophages. Methods: C. fascicularis polyphenols (CFP) were characterized by ultra-performance liquid chromatography (UPLC) combined with quadrupole-time-of-flight mass/mass spectrometry (Q-TOF-MS/MS). The THP-1 cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The NF‐κB/MAPK signaling pathway is involved in the development and progression of cholecystitis (Gao et al., 2022). To further investigate the mechanism of KPR in cholecystitis, we examined the expression levels of NF‐κB/MAPK signaling pathway‐related proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NF‐κB/MAPK signaling pathway is involved in the development and progression of cholecystitis (Gao et al., 2022). To further investigate the mechanism of KPR in cholecystitis, we examined the expression levels of NF‐κB/MAPK signaling pathway‐related proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the cell inflammation of human gallbladder epithelial cells (HGBECs) induced by LPS stimulation is a method to construct an in vitro model of cholecystitis (Zheng et al., 2023). MAPK/NF‐κB signaling has been proven to be involved in the development of cholecystitis by regulating the expression of inflammatory factors (Gao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…38,39 C. fascicularis phenolics-rich extract down-regulated the expression of TNF-α, IL-6, and IL-1β while up-regulating the expression of IL-10 in lipopolysaccharide-induced human monocytes (THP-1) macrophages. 40 It was suggested that phenolics in Camellia extracts, such as catechins, ellagitannin, and flavonoid glycosides, contributed to the anti-inflammatory properties.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, anti-inflammation, antioxidation, and antitumor effects of C. fascicularis polyphenols and flavonoids have been reported [1][2][3]. Therefore, the artificial cultivation of C. fascicularis is not only beneficial to its restoration and protection as a plant species with extremely small populations (PSESPs), but also provides a material guarantee for the development and utilization of C. fascicularis resources in the future.…”
Section: Introductionmentioning
confidence: 99%